Application of Immune Feedback Control Algorithm Based on BP Network Approximation in Intelligent Vehicle Steering System - Lan, Yanting; Chen, Xiaodong (International Journal of Online and Biomedical Engineering (iJOE), 2019)
Abstract—Steering system of intelligent vehicle is very difficult to execute precise control in driving due to many known and unknown disturbances. Therefore, design of steering algorithm has to be feasible for uncertain external interference, such as uneven pavement and horizontal wind, with automatic correction function for changes in the location of intelligent cars caused by road tilt and horizontal wind. As traditional PID control is impossible to meet the control requirements, according to mechanism of biological immunity, an immune feedback control method was proposed to approximate nonlinearity of T and B cells by BP network. Joint simulations of serpentine condition were carried out by Carsim and Simulink. The results show that trajectory tracking error, operating load, risk of rollover and slip and control stability of control system are synthetically evaluated. The comprehensive evaluation index of automatic steering algorithm under high speed operation is fairly advantageous. Experimental results also show that the algorithm effectively realizes tracking of intelligent vehicle for marking lines and avoidance of obstacles.